Empirical insights on national policy styles and political regimes - Howlett, Michael; Tosun, Jale (Policy styles and policy-making, 2018)
This final chapter discusses the working hypothesis addressed by each of the core chapters in this volume: namely, that policy styles vary both among and within regimes. To this end, we have compiled the various explanations offered by the contributors regarding the national policy styles of the 16 countries analyzed. Next, we have provided an integrated discussion of the factors that explain the types of - and possible changes to - national policy styles. The ensuing insights are then explored in a more differentiated manner, in order to better understand how the general model of policy styles relates to the original concept as propounded by Richardson et al. (1982). Finally, the chapter presents ideas for further research in this area.
Gesehen am 27.06.2023